Wspólne dziedzictwo kulturowe jako pomost porozumienia mieszkańców ziemi lubuskiej = Mutual cultural inheritance as an agreement platform of the inhabitants of the Lubuskie region - Nitschke, Bernadetta (1964- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
As opposed to Germany, in Poland there was little interest in a local identity for a long time. The 1960s brought about terms such as ?private homeland? or ?ideological homeland?, which were introduced by researchers. Those notions were not significant from the point of view of a socialistic country. Poland was supposed to be a homogeneous and uniform country as far as national values were concerned. This mostly applies to western and northern territories, which became part of Poland after World War II.
Keywords: ziemia lubuska; historia; po 1944 r.; przesiedlenia; osadnictwo - Polska - 20 w.